Genetic diversity among populations in Scotch pine (Pinus silvestris L.) seed stands of Western Black Sea Region in Turkey - Şevik, Hakan; Ayan, Sezgin; Turna, İbrahim; Yahyaoğlu, Zeki (Genetic diversity among populations in Scotch pine (Pinus silvestris L.) seed stands of Western Black Sea Region in Turkey”, African Journal of Biotechnology Vol. 9(43), pp. 7266-7272, 25 October., 2010)
The aim of this study was to determine the differences among some of the registered seed stands in the Western Black Sea Region in Turkey by means of the morphological characters. The number of 18 morphological characters were designated by measuring and observing on seed (seed length, seed width, seed color and 1000 seed weight), juvenile seedling (root length, hypocothyl length, epycotyl length, cotyledon number, cotyledon length, stem and root dry weight) and seedling (root-collar diameter, number of branches, bud number, stem length, root length, stem and root dry weight) from 9 seed stands in the Western Black Sea Region of Turkey. The obtained data was analyzed by using cluster and penrose analysis. Cluster and penrose analysis showed that there were significant differences within the Pinus sylvestris stands for the morphologic characters.
Keywords: Genetic diversity, Pinus sylvestris, Scotch pine, morphological characters.